1990
DOI: 10.1111/j.1398-9995.1990.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hay fever with loratadine ‐ a new non‐sedating antihistamine

Abstract: The efficacy and safety of loratadine, a new orally active specific H1-receptor blocking antihistamine with poor penetration into the CNS, was evaluated in a double blind comparative study. One hundred and seven hay fever patients, sensitive to birch pollen, were randomized into three parallel groups receiving loratadine 40 mg once daily, clemastine 1 mg twice daily, or placebo during the birch pollen season. Both active treatments showed reduction of symptoms in comparison with placebo, but the results were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…'5 • 16 Histamine is also an important mediator in patients with allergic rhinitis as shown by the effect of HI-antihistamine drug such as loratadine. 17 In conclusion, we found that the nasal passage patency in allergic guinea pigs with the use of AR was reduced by antigen challenge. The effects of antigen challenge were blocked by pretreatment with ketotifen.…”
Section: Discussionmentioning
confidence: 60%
“…'5 • 16 Histamine is also an important mediator in patients with allergic rhinitis as shown by the effect of HI-antihistamine drug such as loratadine. 17 In conclusion, we found that the nasal passage patency in allergic guinea pigs with the use of AR was reduced by antigen challenge. The effects of antigen challenge were blocked by pretreatment with ketotifen.…”
Section: Discussionmentioning
confidence: 60%
“…Cetirizine and loratadine are two secondgeneration antihistamines widely used to treat allergic rhinitis and urticaria (6)(7)(8)(9)(10)(11)(12)(13). Peak plasma concentration occurs about 1 h after intake for both antihistamines (14,15).…”
mentioning
confidence: 99%
“…These findings suggest antihistamines may cause weight gain. However, a previous study showed no weight gain with second generation antihistamines loratadine and clemastine in patients with hay fever (Irander et al 1990). Loratadine dose does not seem to have an impact on weight gain as demonstrated by our results.…”
Section: The Effect Of Antihistamine On Weightmentioning
confidence: 94%